The Value of Common Bracken Revisited - Barbara Turk Niskač (Suomen Antropologi)
Based on a walking ethnography, this photo essay employs sensory ethnography to explore multispecies relationality in steljniki, plots of land traditionally used for grazing and the harvesting of common bracken. Through work in subsistence-based extensive farming, humans have formed multispecies relationality, and, beyond use value, have attributed aesthetic value to the cultivated landscape. This essay presents the micro-processes of relational, affective, and material entanglements of humans with more-than-human worlds in steljniki, particularly with common bracken.